2013
DOI: 10.1186/1752-1505-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Madness or sadness? Local concepts of mental illness in four conflict-affected African communities

Abstract: BackgroundConcepts of ‘what constitutes mental illness’, the presumed aetiology and preferred treatment options, vary considerably from one cultural context to another. Knowledge and understanding of these local conceptualisations is essential to inform public mental health programming and policy.MethodsParticipants from four locations in Burundi, South Sudan and the Democratic Republic of the Congo, were invited to describe ‘problems they knew of that related to thinking, feeling and behaviour?’ Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 43 publications
9
101
4
1
Order By: Relevance
“…For example, client factors such as perceptions of psychological difficulties, shame and stigma associated with mental illness, mistrust of counseling services, English proficiency, stronger reliance on other sources of help, and culturally congruent coping methods have been identified as hindrances for international students in obtaining counseling (Mori, 2000). Among African communities, for instance, research has shown that Africans may not consider less severe distress as "medical" or worthy of intervention but rather wait for psychological distress to become severe prior to seeking treatment (Ventevogel, Jordans, Reis, & de Jong, 2013). Moreover, unavailability of therapists who are culturally similar and competent, and nonexistence of counseling services in students' home countries may deter students from seeking counseling (Mori, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…For example, client factors such as perceptions of psychological difficulties, shame and stigma associated with mental illness, mistrust of counseling services, English proficiency, stronger reliance on other sources of help, and culturally congruent coping methods have been identified as hindrances for international students in obtaining counseling (Mori, 2000). Among African communities, for instance, research has shown that Africans may not consider less severe distress as "medical" or worthy of intervention but rather wait for psychological distress to become severe prior to seeking treatment (Ventevogel, Jordans, Reis, & de Jong, 2013). Moreover, unavailability of therapists who are culturally similar and competent, and nonexistence of counseling services in students' home countries may deter students from seeking counseling (Mori, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Some argue that sociocultural differences in symptomatology and culture are not suffi ciently taken into consideration by global mental health initiatives such as the mhGAP programme (Bass et al, 2007;White & Sashidharan, 2014), despite the fact that there are important variations in how mental distress presents and is experienced (Fernando, 2012;Kohrt et al, 2014;Patel, 1995;Ventevogel et al, 2013).…”
Section: Medicalization: a Potential Drawback Of Mhgapmentioning
confidence: 98%
“…depression, anxiety disorder, or harmful use of substances or alcohol), would not conceptualize their problem as a medical disease, but rather frame their problem in non-medical terms. This would occur, utilizing culturally relevant labels and causal explanations for their distress as being inextricably linked to life experiences or misfortune (Aggarwal, 2014;Patel 1995;Ventevogel et al, 2013).…”
Section: Engaging Communities To Be Partners In Psychosocial Intervenmentioning
confidence: 99%
“…It can be difficult to determine whether non-specific but chronic somatic complaints (including generalized pain, weakness and fatigue, and a weakened immune response) arise from physical damage caused by prolonged torture and incarceration in poor conditions, or have their origins in emotional distress (de C Williams & Baird, 2016). Such determinations are further complicated in sub-Saharan Africa where emotional distress is often communicated through idioms rooted in the body (Ventevogel, Jordans, Reis & de Jong, 2013).…”
Section: Results Of Case File Reviewmentioning
confidence: 99%